Work-life Balance and Organizational Commitment: a Study of Field Level Administration in Bangladesh. Issue 14 (26th October 2021) - Yang, Yumei; Islam, Dewan Md Tajul
ABSTRACT: This article aimed to explore the influence of job pressure stress and workplace support on work-life balance and affective organizational commitment among the officers working in field administration. Using a quantitative method, we collected a sample of 157 out of 563 field administration in Bangladesh. The data were analyzed using multiple regression. The results showed that job pressure stress is negatively related to work-life balance. Family supportive organizational policies has a more pronounced influence on work-life balance than other types of workplace support. Surprisingly, affective organizational commitment is not influenced by work-life balance. Our findings provide a preliminary understanding of work-life balance among public servants in Bangladesh and offer practical advice to policy makers aimed at improving public servants' work-life balance.